1983
DOI: 10.1172/jci111054
|View full text |Cite
|
Sign up to set email alerts
|

Muscle protein turnover and glucose uptake in acutely uremic rats. Effects of insulin and the duration of renal insufficiency.

Abstract: A B S T R A C T Acute renal failure (ARF) in rats is associated with increased amino acid release from peripheral tissues and insulin resistance. To study whether abnormal protein and carbohydrate metabolism are linked in ARF, the effects of insulin on net muscle protein degradation (T) and on glucose uptake were measured in the perfused hindquarters of paired ARF and sham-operated (SO) rats. The basal rate of T increased 40% after 24 and 98% after 48 h of ARF. Insulin was less effective in decreasing T in ARF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(27 citation statements)
references
References 36 publications
(48 reference statements)
0
27
0
Order By: Relevance
“…Previously, we found that the rate of muscle protein degradation was positively correlated with the ratio ofglycolysis (or lactate release) to glucose uptake in muscles of normal rats and rats responding to catabolic conditions (9,25,26). DCA did not significantly change the rate of muscle protein degradation even though it sharply reduced this ratio.…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we found that the rate of muscle protein degradation was positively correlated with the ratio ofglycolysis (or lactate release) to glucose uptake in muscles of normal rats and rats responding to catabolic conditions (9,25,26). DCA did not significantly change the rate of muscle protein degradation even though it sharply reduced this ratio.…”
Section: Discussionmentioning
confidence: 91%
“…Unfortunately, the amount of muscle and the methods required to measure these responses in the same muscle prevented us from arriving at an easy answer. However, we predict that these changes occur in most types of skeletal muscle for the following reasons: (a) The epitrochlearis muscle we used to measure protein degradation and the gastrocnemius used for RNA analyses contain both red and white types of muscle fiber (33,39), and protein degradation in mixed-fiber muscles responds similarly to fasting and acute uremia (28,40); (b) we found that mRNAs of ubiquitin and proteasome subunits in the predominantly white-fiber EDL and mixed-fiber gastrocnemius muscles increase in response to acidemia and glucocorticoids (41); and (c) in response to another catabolic condition, starvation, protein degradation and mRNAs of components of the ubiquitinproteasome system are increased in EDL and in the red-fiber soleus muscle of rats (30,42).…”
Section: Discussionmentioning
confidence: 99%
“…Protein synthesis was calculated by measuring the rate of incorporation of U-'4C-phenylalanine into muscle protein and dividing it by the specific radioactivity (0.1 mCi/mmol) of phenylalanine in the media (16,17). PD was determined in separate experiments by measuring the rate of release of tyrosine into the media in the presence of 0.5 mM cycloheximide.…”
Section: Methodsmentioning
confidence: 99%
“…Glucose was measured using a Beckman Glucose II analyzer (Beckman Instruments, Inc., Palo Alto, CA), which we have found to have a coefficient of variation of 1.5% with glucose measured enzymatically (17). Urea nitrogen appearance was calculated as the algebraic sum of urea nitrogen excretion, and the change in the urea nitrogen pool which was measured as the product of plasma urea nitrogen and the volume of distribution of '4C-urea (35).…”
Section: Methodsmentioning
confidence: 99%